Visible-Light-Induced Three-Component Reactions of α-Diazoesters, Indazoles, and Cyclic Ethers - Wang, Wei; Liu, Yan; Yang, Qin; Fu, Yang; Ding, Qiuping; Peng, Yiyuan (Synthesis, 2024)
An efficient method was developed for the construction of N-short-chain ether-attached carbonyl group-substituted indazoles. The visible-light-induced three-component reactions of α-diazoesters, indazoles, and cyclic ethers, under extremely mild conditions, led to the corresponding mixture of N1 and N2 short-chain ether-substituted indazoles in good to excellent yields.
Keywords: visible-light catalysis; α-diazoester; indazole; cyclic ether; multicomponent reaction